Mengetahui Sejauh Mana Penggunaan Media Kartu Bergambar Untuk Meningkatkan Kemampuan Membaca Huruf Anak Usia 5-6 Tahun Di TK Dharma Wanita Persatuan 2 Purwodadi - Ismania, Nurul; Muntomimah, Siti; Anggraini, Henni (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
The low ability to read letters at preschool age, it should be a special concern. Indeed, the educational materials provided by the teacher do not arouse the decline in students' interest in learning to improve children's ability to read letters, this includes the ability to read the ability to identify various known letter symbols, recognize the initial letter sounds of the names of objects around them, give names to pictures whose initial sounds or letters are similar, also understand the relationship between sounds and letter symbols. Using picture card media, according to the author, as a learning support tool can help children improve their reading skills. This study aims to identify the effect of using picture word cards on the reading ability of children aged 5-6 years at Dharma Wanita Persatuan 2 Purwodadi Kindergarten. The research was conducted at Dharma Wanita Persatuan 2 Purwodadi Kindergarten using a multi-method research approach. The sample of this study amounted to 22 children in group B of Dharma Wanita Persatuan 2 Purwodadi Kindergarten. This classroom action research activity begins with action planning (planning), implementing action (acting), observing (observing), and reflecting (reflecting). This activity then rotates until the expected results. This research uses the PTK model, collaborative Classroom Action Research, where researchers and teachers work together to solve classroom problems. In the first cycle of meetings, an average of 52.2% was obtained, and in the second cycle of meetings, an average of 69.9% was obtained. In the second cycle of meetings, the average obtained 75%, and increased to 80.1% when obtaining a score of 75%. The results showed that children aged 5-6 years at Dharma Wanita Persatuan 2 Purwodadi Kindergarten, Malang Regency could improve their literacy skills by playing picture cards. Based on the results of research and discussion about the application of picture card playing activities to improve the ability to read letters in Group B children at Dharma Wanita Persatuan 2 Purwodadi Kindergarten, Malang Regency can be concluded, literacy skills with picture card playing activities based on the results of cycle I 52.2%, then cycle II 80.1% this shows if there is an increase of 27.9%.